The effect of a heavy resisted sled-pull mesocycle on sprint performance in junior Australian Football players - Edwards, T.; Piggott, B.; Banyard, H. G.; Haff, G. G.; Joyce, C. (The Journal of Strength and Conditioning Research, 2023)
This study assessed the effect of heavy resisted sled-pull training on sprint times and force, velocity, and power characteristics in junior Australian football players. Twenty-six athletes completed a 6-week resisted sled-pull training intervention which included 10 training sessions and 1-week taper. Instantaneous velocity during 2 maximal 30 m sprints was recorded 1 week before and 1 week after the intervention with a radar gun. Velocity-time data were used to derive sprint performance and force, velocity, and power characteristics. A paired t-test assessed the within-group differences between preintervention and postintervention testing. Statistical significance was accepted at p = 0.05. Hedges' g effect sizes (ESs) were used to determine the magnitude of change in dependent variables. Maximum velocity (ES = 1.33) and sprint times at all distances (ES range 0.80-1.41) significantly improved after heavy resisted sled-pull training. This was reflected in sprint force, velocity, and power characteristics with significant improvements in relative theoretical force (ES = 0.63), theoretical velocity (ES = 0.99), relative maximum power (ES = 1.04), and ratio of horizontal to vertical force (ES = 0.99). Despite the multifactorial nature of training and competing physical demands associated with preseason training, these findings imply that a short, resisted sled-pull training mesocycle may improve sprint performance and underlying force, velocity, and power characteristics in junior athletes.